Parties, rituals and symbolisms in schools - Valencia Aguirre, Ana Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper aims at analyzing school parties from interaction spaces and principals’ narratives in six schools in the state of Jalisco. A party is a ritual where participants share symbols related to imaginary –hence the importance of conducting an analysis for understanding institutions as a symbolic framework. A core argument is that established actors are configured from symbolic practices in the institutional space (schools). The repetition of these practices awash with symbolism leads to daily rituals or micro rituals that are ratified in institutions. Methodologically, interviews and non-participant observation in school interaction spaces were used. Based on the findings, it may be stated that the nuclear family, rooted in the Christian image in which authority is a central point, becomes a fundamental factor in shaping institutional life as well as the imaginary linked to school parties.